2015
DOI: 10.1039/c5ra12795e
|View full text |Cite
|
Sign up to set email alerts
|

The origin for highly enantioselective induction of 1-naphthol to isatin-derived N-Boc ketimines catalyzed by quinine thiourea catalyst: an experimental and computational study

Abstract: An enantioselective aza-Friedel-Crafts reaction of 1-naphthol with isatin derived N-Boc ketimines by cinchona based bifunctional thiourea as organo-catalyst is reported. In general the derivatives of Betti base are formed in excellent enantioselectivities (95-99%) with high yields (<99%). The combination of experimental and computational studies have revealed the origin of the stereoselectivity of the aza-Friedel-Crafts reaction of 1-naphthol with isatin derived N-Boc ketimines by cinchona based bifunctional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…Otherhand, we found that the nitroolefin activated by tertiary amine of organocatalyst OC‐7 via abstracting of proton from methyl group of nitroolefin (Figure ). Based on these experimental data we have proposed the catalytic cycle of this reaction as shown in the Scheme …”
Section: Resultsmentioning
confidence: 99%
“…Otherhand, we found that the nitroolefin activated by tertiary amine of organocatalyst OC‐7 via abstracting of proton from methyl group of nitroolefin (Figure ). Based on these experimental data we have proposed the catalytic cycle of this reaction as shown in the Scheme …”
Section: Resultsmentioning
confidence: 99%
“…The most efficient bifunctional cinchona thiourea system was reported for the reaction of 1-naphthol with isatin derived N-Boc ketimine derivatives to provide products in excellent yields (99%) and enantioselectivity (up to 99%) (Scheme 55). [69] However, the compound with R 1 =H was observed to give reduced ee of 63%. Based on the kinetics, NMR experiments and DFT studies, the origin of stereoselectivity using bi-functional cinchona thiourea catalyst for the reaction of 1-naphthol with isatin derived N-Boc ketimine derivatives was unravelled.…”
Section: Cinchona Alkaloid Derivativesmentioning
confidence: 98%
“…The thiourea catalyst is responsible for the preorientation and activation of the substrates performing as a bifunctional organocatalyst. Phenylglyoxal is activated after construction of hydrogen bonds between the carbonyl groups of 162 and thiourea scaffold, whereas the 1‐naphthol endures nucleophilic activation through hydrogen bonding with the quinuclidine scaffold of the catalyst . The C‐2 carbon atom of 155 attacks the Re face of 162 , therefore explaining the detected stereo and regioselectivity …”
Section: Organocatalyzed Asymmetric Friedel‐crafts Reactions Usingmentioning
confidence: 99%